2018
DOI: 10.1242/jcs.221994
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive P2Y2 receptor activity regulates basal lipolysis in human adipocytes

Abstract: White adipocytes are key regulators of metabolic homeostasis, which release stored energy as free fatty acids via lipolysis. Adipocytes possess both basal and stimulated lipolytic capacity, but limited information exists regarding the molecular mechanisms that regulate basal lipolysis. Here, we describe a mechanism whereby autocrine purinergic signalling and constitutive P2Y 2 receptor activation suppresses basal lipolysis in primary human in vitro-differentiated adipocytes. We found that human adipocytes poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
4
18
0
1
Order By: Relevance
“…In accordance with recent studies, AR-C118925 was chosen for blockage of the upregulated P 2 Y 2 Rs. 8,18,19,36 The results of the current study showed attenuation of bilateral hypersensitivity after AR-C118925 was administered ipsilateral to the inflammation. This suggests that the analgesic effect of AR-C118925 on ipsilateral MM hypersensitivity may be mediated by its effect on P 2 Y 2 Rs.…”
Section: Controlsupporting
confidence: 51%
See 1 more Smart Citation
“…In accordance with recent studies, AR-C118925 was chosen for blockage of the upregulated P 2 Y 2 Rs. 8,18,19,36 The results of the current study showed attenuation of bilateral hypersensitivity after AR-C118925 was administered ipsilateral to the inflammation. This suggests that the analgesic effect of AR-C118925 on ipsilateral MM hypersensitivity may be mediated by its effect on P 2 Y 2 Rs.…”
Section: Controlsupporting
confidence: 51%
“…According to a recent study, the constitutive P 2 Y 2 Rs activity produces intracellular Ca 2+ tone and suppresses basal lipolysis via an adenylate cyclase-dependent mechanism in human adipocytes. 18 Muoboghare et al have suggested that UTP acts via P 2 Y 2 Rs to mobilise Ca 2+ in human endothelial cells. 19 Recent studies have investigated the role of P 2 Y 2 Rs in pain mechanisms, but their exact function remains unclear, especially in the fields of orofacial pain and TMD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been reported that constitutive P2Y 2 receptor activity suppresses basal lipolysis in human adipocytes. Ali et al (58) showed that pharmacological antagonism or knockdown of P2Y 2 receptor increases intracellular cAMP levels and enhances basal lipolysis. They also observed that acute enhancement of basal lipolysis following P2Y 2 receptor antagonism alters the profile of secreted adipokines leading to long-term adaptive decrease in lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that acute enhancement of basal lipolysis following P2Y 2 receptor antagonism alters the profile of secreted adipokines leading to long-term adaptive decrease in lipolysis. Based on their findings, Ali et al (58) concluded that basal lipolysis and adipokine secretion are controlled by autocrine purinergic signaling in human adipocytes. Our above observations on the alterations in plasma lipids and adipokines in P2Y 2 receptor KO mice fed high-fat diet are consistent with this report.…”
Section: Discussionmentioning
confidence: 99%
“…Perivascular adipose tissue (PVAT), a layer of fatty tissue which surrounds blood vessels, is now known to release a variety of adipokines and other factors which regulate vascular tone [87,88]. Adipose tissue expresses P2 receptors which can be activated by ATP released from perivascular sympathetic nerves to regulate lipolysis [89][90][91], and there is evidence for constitutive release of nucleotides from adipocytes in regulation of lipolysis [92]. In obesity, the increase in adipocyte area and mass leads to hypoxia [88].…”
Section: Roles Of Purines In the Cardiovascular Systemmentioning
confidence: 99%